Optimalisasi Transformasi Digital pada Strategi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) di Kota Bandarlampung - Jihan Fatin Fadillah Lotte; Reni Oktavia; Ratna Septiyanti; Aryan Danil Mirza BR (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research aims to describe the implementation of digital transformation in marketing strategies among micro, small, and medium enterprises (MSMEs) in the culinary sector, using Nomnom Kitchen in Bandarlampung City as a case study. Employing a qualitative approach with data collection techniques including interviews, observations, and documentation, the research explores the firsthand experiences of business actors in transitioning from conventional to digital marketing. The findings reveal that MSME actors face complex dynamics throughout the digitalization process, involving internal challenges such as limited human resources and digital content management, as well as external opportunities like expanded market reach. Digital transformation emerges as a strategic tool that enhances promotional efficiency, strengthens customer engagement, and fosters a business model that is more responsive to technological advances. The study highlights the importance of digital training and the enhancement of entrepreneurial capacity to optimize the digital potential of MSMEs.